Experience with endoscopic resection of oesophageal verrucous carcinoma and literature review. Issue 6 (21st June 2019) - Soota, Kaartik; Tirumanisetty, Pratyusha; Lee, Ye Jin; Holm, Adrian
Abstract : A 65-year-old male patient with chronic dysphagia was found to have a 2 cm mass at gastro-oesophageal junction on endoscopy. Biopsy showed squamous hyperplasia without malignancy. Controlled radial expansion balloon dilatation and partial resection were performed but the symptoms recurred. He finally underwent endoscopic mucosa resection and histology showed well-differentiated verruciform squamous proliferation limited to the mucosa. Small amounts of tumour remnants were treated during subsequent follow-up endoscopies and the patient has been tumour free since then. Diagnosis of oesophageal verrucous carcinoma can be challenging and could be managed with endoscopic resection. In this report, we review the literature and present our experience with a patient with oesophageal verrucous carcinoma.